La incidencia de la inversión pública en la pobreza multidimensional de la Macro Región Norte en el Perú período 2008 - 2015 - Graus Rios, Adan (2016)
The present research aims to analyze how public investment affects the multidimensional poverty of the northern region of Peru in the period 2008-2015; For which we used a non-experimental research approach of longitudinal and transverse cutting, therefore to determine the incidence we used an econometric model fixed effects panel data's so we used the theoretical framework information. For the elaboration of the results a descriptive analysis of the public investment and the index of multidimensional poverty was realized, then the econometric model Fixed effects panel data's. It was found that, in the face of an increase in public investment, there is a reduction in the multidimensional poverty index, ie if public investment increases by 1% in the northern macro region, the multidimensional poverty index will decrease by 0.38%; On the other hand, it was found that the departments of Ancash, La Libertad, Lambayeque, Piura and Tumbes, faced with an increase in Public Investment, there was a reduction in the multidimensional poverty index, the opposite occurred for the departments of Amazonas, Cajamarca, San Martin, That is, that increases in public investment did not have a positive impact on poverty reduction.